010 Real-world experience with ocrelizumab in the MSBase registry – Australian RRMS cohort. (23rd August 2021) - Butzkueven, Helmut; Spelman, Tim; Kalincik, Tomas; Buzzard, Katherine; Walt, Anneke Van der; Lechner-Scott, Jeanette; Hodgkinson, Suzanne; Butler, Ernest; Macdonell, Richard; Slee, Mark; Group, MSBase Study; Marcel, Bruno
Abstract : Introduction: Ocrelizumab (OCR) is a humanised anti-CD20 + monoclonal antibody for the treatment of Multiple Sclerosis. Objectives: In Australian MSBase clinics, we describe baseline characteristics of relapsing-remitting MS (RRMS) patients treated with OCR, treatment pathways and early clinical outcomes. Methods: Secondary analysis using MSBase Registry data for RRMS patients with OCR initiation within 3 months of MSBase recorded visit. Descriptive statistics included demographics, disease course/duration, prior disease modifying therapies (DMT) and EDSS. Relapse data was described in patients with ≥6 months follow-up. Results: As of 4 June 2020, MSBase included 624 eligible Australian RRMS patients newly treated with OCR. Median age at OCR initiation was 42.5 years. OCR was first line therapy in 18.9% of patients. Most frequent DMT's in the 12 months prior to OCR were natalizumab (32.1%) and fingolimod (24.8%). Of 434 RRMS patients with ≥6 months follow-up, 392 remained relapse free (90.3%; 95% CI 81.6, 99.7) over a mean OCR exposure of 1.35 years. In this group, the annualized relapse rate (ARR) was 0.10 (95% CI 0.08-0.13), compared to an ARR of 0.83 in the 24 months pre-OCR start. Treatment discontinuation was recorded for 20 of these 434 patients In the overall RRMS cohort, treatment persistence at 12 and 24 months was 94.3% (95%CI: 90.9%-96.1%%) and 88.7% (95%CI 77.2%-94.0%), respectively. Conclusion: Almost 20% of RRMS patients treated with OCR in Australian MSBase centres received OCR as a first line treatment. During OCR treatment, relapses and OCR discontinuations were rare.